The Impact of Teacher Quality on Student Motivation, Achievement, and Persistence in Science and Mathematics - Adem Ekmekci; Danya Marie Serrano (MDPI AG, 2022)
Science, technology, engineering and mathematics (STEM) fields occupy a significant role in human prosperity and advancement. This study explores the factors affecting student STEM outcomes. Traditionally, the associations of students' own motivational or cognitive inputs to their STEM career outcomes have been investigated before. Similarly, association of teacher quality to student achievement outcomes have been made before. This paper presents a novel approach by introducing teacher quality as the contextual factor within the social cognitive career theoretical (SCCT) model using a comprehensive and robust model for teacher quality including teachers' motivation, qualifications, and self-reported practices. This study examines the extent to which high school students' mathematics and science teachers' beliefs, professional background, and instructional practices relate to students' motivation, achievement, and future career plans in STEM using a nationally representative, large dataset: High School Longitudinal Study 2009. The results indicate that science and mathematics teachers' professional background, motivational beliefs, and self-reported instructional practices have significant impact on students' motivation, persistence, and achievement outcomes in science and mathematics. No direct impact of teacher factors on STEM career plans are found; however, students motivational and achievement outcomes (impacted by teacher factors) do have significant impact on students' career plans in STEM.